Perempuan dan Politik di Media Sosial; Twitter Settimen terhadap #megawati dalam Pendekatan Netnografi - Suharnanik .; Umar Sholahudin (Universitas Wijaya Kusuma Surabaya, 2023)
The query #megawati was posted by the proprietor of Twitter. The quotes are the reactions offered by netizens to these posts in their comments. The general public, or netizens, give their remarks, which might be seen as popular opinion against Megawati. Public opinion can take the form of information that is given, passion that is donated in the form of knowledge, or feelings that are felt in order to support the citizen community's behavior. The purpose of this study is to analyze #megawati data from Twitter in order to describe the image of women in politics. This study employs a netnographic approach, retrieving #megawati data from Twitter and analyzing the qualitative data with Atlas.ti version 9 software. The findings of this study will be presented in the form of a flowchart, which is a visualization of qualitative data from 100 tweets. Furthermore, data analysis of existing references about the opportunities for women to rule. This study is unique and intriguing because it has never been done before. It delves into the most recent incident, in which Megawati's speech was widely circulated, causing social media to erupt with various quotations, statuses, mentions, and hashtags. According to the findings of this study, there are more quotes that lead to positive opinions than those that are neutral or contain negative opinions. More research on women and politics should be conducted in the future using other social media platforms such as Facebook, Instagram, and Tiktok. In order to provide a more diverse comparison of Indonesia's political situation for women.Keywords: twitter, netnography, #megawati.